DEVELOPMENT OF EFFECTIVE METHODS AND MEANS FOR INFORMATION OBTAINING AND PROTECTION: PHYSICAL MODEL OF BIOSENSOR AND DATA CODING - Klyuchko, Olena; Shutko, Vladimir; Morozova, Irina; Beletsky, Anatoly (Ukrainian Information Security Research Journal, 2021)
The purpose of this work is detailed description of technical devices - biosensors as element of biomedical information systems, analysis of electrical information signals at output of biosensor, its ability to encode information and data protection in such system. Methods of physical modeling of biosensor were applied, including modeling of neuro-like biosensor (NBS) as potential electronic device and element of information systems, development of information system for monitoring with databases, methods of comparative analysis of the characteristics of output electrical information signals of biosensor; its physical and mathematical models were developed as well. The concept of biosensors and their general characteristic were given, the prototypes were observed. The physical model of biosensor NBS was developed and test results of this device in conditions of some chemical substances input influences were given. The example of NBS practical application and some results of its testing for coding of one of chemical substance as relative electric current were demonstrated. The neuro-like biosensor NBS was examined as abstraction in consistent unity of its functions: signal receiver – filter – analyzer – encoder / decoder. Each function and, accordingly, each of the above mentioned blocks were characterized. Possibilities of information coding by biosensor within the following model were considered – at NBS input the information were accepted being coded in the form of chemical structures of acting substances or in the form of electric signals with the set characteristics, after recoding the output information arrived in the form of electric signals with changed characteristics. It is shown that the reverse phenomenon – decoding of information – is possible too. A brief mathematical description of this biotechnical device functioning was given as well as corresponding algorithm. It was shown that the functions of NBS biosensor for encoding / decoding can be expressed in two forms that can be applied in practice: in tabular form and in analytical form as a function or several functions. Some parts of performed work were theoretical. As a result of performed works the possibilities of application of this technical device - biosensor for coding of information signals were substantiated. Thus, our obtained results can be used to encode and transmit information on relevant chemicals. The proposed work opens new opportunities for information security in information systems.